The AHA Recommendations for a Healthy Diet and Ultra-Processed Foods: Building a New Diet Quality Index - Cacau, Leandro Teixeira; Marcadenti, Aline; Bersch-Ferreira, Angela Cristine; Weber, Bernardete; Almeida, Jussara Carnevale de; Rodrigues, Cíntia Corte Real; Lotufo, Paulo Andrade; Bensenor, Isabela Martins; Marchioni, Dirce Maria (Frontiers in Nutrition, 2022)
The American Heart Association (AHA) has developed the concept of “ideal cardiovascular health” (ICH), a seven-component score, which includes health dietary metrics. Higher ultra-processed foods intake is related with several cardiometabolic and cardiovascular diseases. We propose to develop and validate the Cardiovascular Health Diet Index (CHDI), a diet quality index that combines the AHA's recommendations of a healthy diet for cardiovascular health and ultra-processed foods. We used dietary data obtained through a 114-item FFQ from 14,779 participants of the Brazilian Longitudinal Study of Adults Health (ELSA-Brasil). The CHDI had 11 components and a total score ranging from 0 to 110 points. Validation and reliability analyses were performed, including principal component analyses, association with selected nutrients, means differences between groups (for example, smokers vs. non-smokers), Cronbach’s alpha, and linear regression analyses between CHDI and overall dietary quality. The mean CHDI was 57.1 points (95% CI 47.9:66.0). The CHDI had four dimensions; in addition, it was associated with nutrients related to cardiovascular health, and the points were significantly (p<0.001) lower in smokers (52.1) than in non-smokers (57.8). Cronbach’s alpha value was 0.50. After age and sex adjustment, the CHDI score remained associated with a higher overall dietary quality (β 0.87, 95%CI 0.84:0.89, p <0.001). The CHDI proved to be valid and reliable for use, in addition to being associated with higher overall dietary quality. The use of CHDI is expected to assess the population's compliance with dietary recommendations for promoting cardiovascular health and preventing cardiovascular disease.